CCHFV vaccine development, current challenges, limitations, and future directions - Ahata, Büşra; Akçapınar, Günseli Bayram (Frontiers in Immunology, 2023)
Crimean-Congo hemorrhagic fever (CCHF) is the most prevalent tick-borne viral disease affecting humans. The disease is life-threatening in many regions of the developing world, including Africa, Asia, the Middle East, and Southern Europe. In line with the rapidly increasing disease prevalence, various vaccine strategies are under development. Despite a large number of potential vaccine candidates, there are no approved vaccines as of yet. This paper presents a detailed comparative analysis of current efforts to develop vaccines against CCHFV, limitations associated with current efforts, and future research directions.